Simultaneous Generation of Optimum Pavement Clusters and Associated Performance Models. (12th December 2018) - Khadka, Mukesh; Paz, Alexander; Arteaga, Cristian; Hale, David K.
Abstract : With regard to developing pavement performance models (PPMs), the existing state-of-the-art proposes Clusterwise Linear Regression (CLR) to determine the pavement clusters and associated PPMs simultaneously. However, the approach does not determine optimal clustering to minimize error; that is, the number of clusters and explanatory variables are prespecified to determine the corresponding coefficients of the PPMs. In addition, existing formulations do no address issues associated with overfitting as there is no limit to include parameters in the model. In order to address this limitation, this paper proposes a mathematical program within the CLR approach to determine simultaneously ( 1 ) an optimal number of clusters, ( 2 ) assignment of segments into clusters, and ( 3 ) regression coefficients for all prespecified explanatory variables required to minimize the estimation error. The Bayesian Information Criteria is proposed to limit the number of optimal clusters. A simulated annealing coupled with ordinary least squares was used to solve the mathematical program.